GIMP for Absolute Beginners - Smith, Jan; Joost, Roman (Apress : Imprint: Apress, 2012)
GIMP for Absolute Beginners gives us an easy way to use the power of GIMP, and enjoy digital photography and graphics without worrying about application features. GIMP is a powerful open source graphics and digital imaging application with almost all the features of its proprietary counterpart, Photoshop. But many of us are photographers and artists first, and we like to use our tools without having to think about them too much. GIMP for Absolute Beginners gets us to this stage without patronising users who haven't used GIMP before. But what can we actually do with photos and graphical images? These questions are answered in a photo projects chapter as well as a chapter on digital painting: Starting with making small changes to photos and adding information to them to creating paintings and drawings without photographic input. GIMP for Absolute Beginners covers the newest version of GIMP, version 2.8, so you can be sure the book covers the latest GIMP features. **The print version of this book is black & white, but the ebook version is in color on color-enabled devices. **.